2015
DOI: 10.1097/ajp.0000000000000127
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Anxiety Reduction on Clinical Response to Pediatric Chronic Pain Rehabilitation

Abstract: The findings of this study support existing research on anxiety and CP, specifically the relationship between anxiety and pain-related disability. This study also supports the benefit of intensive interdisciplinary rehabilitation for both reducing anxiety and increasing functional outcomes, suggesting a possible link in children's response to intervention. Study limitations and future directions for related research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 48 publications
2
47
0
Order By: Relevance
“…The systematic review showed large short-term reductions in pain intensity [36]. More recent studies confirm these short-term reductions in pain intensity [28,34,43]. Several studies also provide evidence for long-term reductions (12 to 24–42 months after treatment) of pain intensity [16,28,34,47,52,53].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The systematic review showed large short-term reductions in pain intensity [36]. More recent studies confirm these short-term reductions in pain intensity [28,34,43]. Several studies also provide evidence for long-term reductions (12 to 24–42 months after treatment) of pain intensity [16,28,34,47,52,53].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding pain management, various strategies are taught, such as relaxation techniques [32,33,34,41,49,50], attention defocusing techniques [33,41,49], imagery [32,41,43,49], active daily structures [28,32,33,34,35,41,48,49,50], stress management [32,33,45,49] and problem-solving activities [32,43,49]. Physical therapy [28,32,33,34,35,41,48,49,50], biofeedback [32,33,45,49] and therapy for psychological comorbidities [33,41] such as depression or anxiety are also included in rehabilitation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings from this study also suggest further investigation focused on designing and testing tailored behavioral approaches to target both anxiety and pain symptoms in youth with chronic pain. At present, there is some evidence that improvements in pain can be made when anxiety is addressed at least in an intensive inpatient rehabilitation program that includes CBT (40) Thus, modifications of existing treatment protocols and future examination of the role of anxiety in relationship to pain-focused CBT treatment outcomes in a traditional outpatient setting is warranted.…”
Section: Discussionmentioning
confidence: 99%